Micromolar Affinity and Higher: Synthetic Host-Guest Complexes with High Stabilities - Sarkar, Sayan; Ballester, Pablo; Spektor, Mark; Kataev, Evgeny (Angewandte Chemie International Edition, 2023)
The design of high-affinity synthetic host-guest complexes is of paramount importance because they are key elements in constructing unprecedented supramolecular assemblies, functional materials, molecular probes, artificial signal transduction events, and interfaces with the biological world. The present review article collects recent achievements in the design of 1 : 1 host-guest complexes with outstanding stabilities, i.e., exceeding 10(6) M-1. The relationships between the measured thermodynamic constants and the structural parameters of the interacting species are analyzed. The design features of high-affinity hosts are discussed in light of their binding properties. Different solvents and different types of noncovalent interactions are considered for the stabilization of the complexes. Finally, some hints are provided for the design of future synthetic receptors displaying high affinity and selectivity.
CRIS-Team WoS Importer:2023-05-26